Modelling recorded crime: a full search for cointegrated models - van Velsen, J. L. (2008)
A modelgenerator is developed that searches for cointegrated models among a potentially large group of candidate models. The generator employs the first step of the Engle-Granger procedure and orders cointegrated models according to the information criterions AIC and BIC. Assisted by the generator, a cointegrated relation is established between recorded violent crime in the Netherlands, the number of males aged 15-25 years (split into Western and non-Western background) and deflated consumption. In-sample forecasts reveal that the cointegrated model outperforms the best short-run models.Comment: 6 pages including 1 figure and 4 tables; typos corrected, footnotes change